Congenital toxoplasmosis in infants from chronically infected mothers: report of two cases - Roberta Rassi Almeida; Geovana Batista de Campos; Ana Maria Castro (Revista Paulista de Pediatria)
ABSTRACT Objective: To describe two severe cases of congenital toxoplasmosis in infants born to chronically infected mothers who did not receive education or information on the prevention of gestational toxoplasmosis during prenatal care. Case description: The mothers had a previous serological diagnosis of toxoplasmosis conducted during prenatal care, with non-reactive (<10 IU/mL) IgM and reactive IgG (>10 IU/mL), and were considered “immune” to the infection. Both infants were born with sequelae of the congenital infection, including neurological and ocular alterations. Comments: Managing gestational toxoplasmosis in susceptible pregnant women is a considerable challenge in several countries, especially in South America. It is necessary to diagnose and monitor chronic gestational toxoplasmosis, as it may result from reactivation or reinfection. Both forms can cause sequelae and irreparable damage to newborns. In addition, it is essential to guide all pregnant women on how to avoid contact with Toxoplasma gondii, regardless of their serological status.